2024
DOI: 10.1101/2024.04.23.590801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Dynamic Entropy Approach Reveals Reduced Functional Network Connectivity Trajectory Complexity in Schizophrenia

David Sutherland Blair,
Robyn L. Miller,
Vincent D. Calhoun

Abstract: Over the past decade and a half, dynamic functional imaging has revolutionized the neuroimaging field. Since 2009, it has revealed low dimensional brain connectivity measures, has identified potential common human spatial connectivity states, has tracked the transition patterns of these states, and has demonstrated meaningful alterations in these transition and spatial patterns in neurological disorders, psychiatric disorders, and over the course of development. More recently, researchers have begun to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…The temporal profiles of each subject’s ICNs were detrended, orthogonally aligned with motion parameters, and despiked. Detailed description of data collection, estimation of the functional networks, their functional connectivity and number of temporally independent sources are provided in (Blair et al, 2024; Du et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal profiles of each subject’s ICNs were detrended, orthogonally aligned with motion parameters, and despiked. Detailed description of data collection, estimation of the functional networks, their functional connectivity and number of temporally independent sources are provided in (Blair et al, 2024; Du et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Metrics originating from information theory, particularly those linked with entropy, have shown their ability in extracting meaningful information from underlying brain networks, in both healthy and mental disorder state (Poza et al, 2021). Thus, current study (Blair et al, 2024) tracked subject trajectories in dynamic functional connectivity state space during brain scans evaluating entropy production along each dimension of the proposed basis space. Authors found that schizophrenia patients demonstrate lower entropy, suggesting simpler trajectories compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%